Avaliação de ciclo de vida comparativa dos processos de anodização e oxidação eletrolítica com plasma de liga de alumínio - Gianelli, Bruno Fernando [UNESP] (2014)
The ain of the present was to perform a surface treatment of aluminum alloys through the plasma electrolytic oxidation (PEO) method and implement a life cycle assessment (LCA) comparison between this process and the conventional anodizing. Within this context it was defined a functional unit an aluminum AA5052-H34 sample with 11.1 cm2, whit the PEO process performed using a solution of 20 grams of Na2SiO3 per liter of deionized water and a current density kept at i=0,01 A/cm2. The same solution has been reused for 6 consecutive treatments. The results of film characterization revealed the diverge of the coating properties after the third reutilization of the solution, changing the amount of inputs used to 6.67 g (Na2SiO3) / 333 mL (H2O), affecting the LCA for this surface treatment. Corrosion and wear resistances have been adopted as indicative of the lifetime of samples coated by both methods. According to the results, the corrent relationship between the functional unit of both treatments was defined as 26 anodized as 26 anodized samples to each PEO sample. Based on the above data a LCA was performed for both processes, finding out five relevant impact categories: Fossil Fuels, Inorganic Resp., Carcinogens , Climate Change and Minerals, all them with greater impact on the amodizing. According to the results, it is possible to note a lower environmental impact of PEO surface treatment as compared to conventional anodizing